2020
DOI: 10.1080/15213269.2020.1768122
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between online vigilance and affective well-being in everyday life: Combining smartphone logging with experience sampling

Abstract: Through communication technology, users find themselves constantly connected to others to such an extent that they routinely develop a mind-set of connectedness. This mind-set has been defined as online vigilance. Although there is a large body of research on media use and well-being, the question of how online vigilance impacts well-being remains unanswered. In this preregistered study, we combine experience sampling and smartphone logging to address the relation of online vigilance and affective well-being i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 61 publications
7
36
0
Order By: Relevance
“…Higher mean scores indicate a higher degree of online vigilance. The scale has evidenced sound construct and nomological validity and high internal consistency [46,49,78]. The Cronbach's alpha in the present study was 0.89 (T1) and 0.87 (T2).…”
Section: Methodssupporting
confidence: 47%
See 1 more Smart Citation
“…Higher mean scores indicate a higher degree of online vigilance. The scale has evidenced sound construct and nomological validity and high internal consistency [46,49,78]. The Cronbach's alpha in the present study was 0.89 (T1) and 0.87 (T2).…”
Section: Methodssupporting
confidence: 47%
“…Distraction by smartphone use appears to be activated by internal thoughts or external cues interfering with other tasks, which may be driven by online vigilance-a constant preoccupation with online content, leading to salience, monitoring and prompting urges to check [46], resulting in strong habitual behaviour [47,48]. Salience of online content has been found to be negatively associated with affective wellbeing and life satisfaction, particularly when thoughts are negative [49].…”
Section: Distraction and Its Relation To Other Psychological Constructs In The Smartphone Literaturementioning
confidence: 99%
“…Contributing to this discussion (see also Davidson et al, 2020), the present studies suggest that the pattern of use (e.g., smartphone procrastination) is relatively more influential than the quantity-at least when it comes to academic outcomes. In a similar vein, research has shown that the objective amount of smartphone-use is not robustly associated with individuals' well-being (Johannes et al, 2020;Orben & Przybylski, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement error in logging technology use is a common issue (e.g. [ 12 , 77 ]), and researchers collaborating with industry partners need to understand how these partners collect telemetry. The field needs to embrace these challenges in measurement rather than defaulting to self-reports.…”
Section: Discussionmentioning
confidence: 99%